Effects of HCG on human epithelial ovarian cancer vasculogenic mimicry formation in vivo - GAO, SAINAN (Oncol Lett, 2016)
Ovarian cancer is the leading cause of mortality due to gynecological malignancy, and vasculogenic mimicry (VM) formation is correlated with poor prognosis. In a previous study, the present authors observed that human chorionic gonadotropin (HCG) could promote VM formation in three-dimensional OVCAR-3 cell cultures. In order to investigate whether HCG could promote VM formation in ovarian cancer in vivo, the role of OVCAR-3 cells overexpressing or depleted of chorionic gonadotropin, beta polypeptide 5 (CGB5, which is the fifth subunit of β-HCG and was identified as the key part of HCG) were injected into nude mice in the present study, while BeWo cells were used as a positive control. The results demonstrated that overexpressed CGB5 promoted xenografts tumor formation in nude mice, and the results of hematoxylin and eosin and cluster of differentiation (CD)34-periodic acid-Schiff dual staining revealed that CGB5 promoted VM formation. Furthermore, reverse transcription-polymerase chain reaction and immunochemistry staining demonstrated that the expression of the vascular markers CD31, vascular endothelial growth factor and factor VIII was also upregulated in the CGB5-overexpressing xenografts tumors. In addition, the expression of luteinizing hormone receptor (LHR), the receptor of CGB5, was increased in CGB5-overexpressing cells. In conclusion, CGB5 may promote tumor growth and VM formation via activation of the LHR signal transduction pathway, which may support a novel strategy for ovarian cancer therapy.